Tingkat kesehatan karang berdasarkan coral health chart di tiga daerah penyelaman di Taman Nasional Bunaken - Kamagi, Jongky Wuner Alfius; Djamali, Radjab; Towoliu, Robert Daniel; Polii, Andritsu (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2022)
Bunaken National Park is a special interest tourism destination with diving as the main attraction. Bunaken National Park is not only famous for the diversity of marine life such as fish, mammals, and marine reptiles, but also famous for its unique underwater landscape in the form of coral reef walls which are the main attraction for underwater photographers. The increase in tourist visits has caused damage to the coral reefs on Bunaken Island. Other damages can be caused by nature such as storms, coral disease, starfish abundance, crown of thorn and coral bleaching. Based on these problems, this study set the following objectives: to measure the health level of corals in the Bunaken Island area, Bunaken National Park, North Sulawesi Province. The method used for data collection in this study was to use a coralwatch table with a random sampling method. The results denoted that the Pangalisang and Fukui dive areas were on a scale of 4 while the Muka Kampung area was on a scale of 3.